2020
DOI: 10.1155/2020/8885886
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Lactobacillus plantarum DY-1 Fermented Wheat Germ Extract and Its Influence on Lipid Oxidation and Texture Properties of Emulsified Sausages

Abstract: The nutrient compositions and in vitro antioxidant activities of water-soluble extract from Lactobacillus plantarum DY-1 fermented wheat germ and its effect on the lipid oxidation and texture properties of emulsified sausages were investigated. The optimal hydroxyl radical scavenging capacity of 72.8 ± 2.9% was demonstrated for fermented wheat germ extract (FWGE) by terms of the fermentation conditions as follows: fermentation time of 26 h, fermentation temperature of 35°C, initial pH of 3.0, solid to liquid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…In Wu's study, the amount of phenolic compound, hydroxyl radical scavenging, and peroxide anion scavenging activity in extracts of wheat germ inoculated with L. plantarum tended to increase as the fermentation process proceeded [43]. In the present study, the results of total phenolic contents were inconsistent with DPPH radical scavenging, similar to the results of Wu's study.…”
Section: Chemical Characteristics Of Fermented Oat Extracts By Lc/ Ms...supporting
confidence: 79%
“…In Wu's study, the amount of phenolic compound, hydroxyl radical scavenging, and peroxide anion scavenging activity in extracts of wheat germ inoculated with L. plantarum tended to increase as the fermentation process proceeded [43]. In the present study, the results of total phenolic contents were inconsistent with DPPH radical scavenging, similar to the results of Wu's study.…”
Section: Chemical Characteristics Of Fermented Oat Extracts By Lc/ Ms...supporting
confidence: 79%
“…Antioxidant activity of wheat was improved after fermentation with Lactobacillus species. The improvement in the antioxidant activity of wheat might be due to the increase in the protein content as reported by [33].…”
Section: Antioxidant Activitymentioning
confidence: 74%
“…Biological activities were retained after cooking, despite differences in amino acid compositions and sequences between dough and bread peptides. Wheat germ fermented with Lactobacillus plantarum DY-1 exhibited a hydroxyl radical scavenging capacity of 72.8 ± 2.9% and retarded thiobarbituric acid-reactive substances (TBARSs) formation in emulsified sausages stored at 4 °C for 7 days [ 146 ]. Niu et al [ 147 ] found promising antioxidant activities from peptides (less than 1 kDa) obtained by fermentation of wheat germ with Bacillus Subtilis B1.…”
Section: Production Strategies For Antioxidant Peptidesmentioning
confidence: 99%